Inorganic Molding
By using high-definition calcified carbonate compounds and low-thermal conductivity calcified carbonate compounds in the inorganic molded body, the deformation and crack problems during heating are solved, and the emission of carbonic acid gas is reduced, thereby achieving the improvement of the performance of the inorganic molded body.
Patent Information
- Application Number
- JP2024568143
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-10
- Filing Date
- 2024-07-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The application of seawater residues generated during the production of magnesium hydroxides in the prior art in the application of masonry materials may lead to deformation and cracks during the heating process, and also the problem of carbonic acid gas not being effectively reused.
By adding a high aspect ratio calcified carbonate compound to the inorganic molded body and combining a low thermal conductivity calcified carbonate compound, the surface shrinkage and the back temperature increase during heating are suppressed, thereby reducing deformation and cracks.
It effectively suppresses deformation and cracks of the inorganic molded body during heating, improves thermal insulation performance, reduces thermal shock, and thus improves the overall performance of the inorganic molded body.
Smart Images

Figure 0007662908000005 
Figure 0007662908000006 
Figure 0007662908000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic molded body. [Background technology]
[0002] Inorganic molded bodies are molded bodies that are mostly composed of inorganic substances such as hydraulic materials and siliceous materials, and have properties such as fire resistance, light weight, high strength, and ease of workability, and are therefore widely used for exterior wall materials for houses, roof underlayment materials, eaves ceiling materials, and the like.
[0003] On the other hand, due to the recent increase in environmental awareness, attempts are being made to reuse by-products and by-produced energy, such as waste materials, exhaust gases, and waste heat, which are generated secondarily in industrial processes.
[0004] As a technology for promoting the reuse of waste while improving fire resistance, which is one of the important safety features required for inorganic molded bodies, a technology has been proposed in which seawater residue, which is mainly composed of calcium carbonate and magnesium hydroxide and is by-produced in the process of removing carbonates from seawater, is applied to a calcareous material (JP Patent Publication No. 2012-116685). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-116685 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, even with the above techniques, undesirable thermal behavior such as warping and cracking may occur when heated, and it is therefore necessary to sufficiently suppress the thermal behavior of inorganic molded bodies when used as building materials.
[0007] Furthermore, carbon dioxide is becoming widely recognized as a greenhouse gas, and reuse and reduction of carbon dioxide emissions as a secondary product from industrial processes have become urgent issues.
[0008] An object of the present invention is to provide an inorganic molded article that can sufficiently reduce warping and cracking when heated when used as a building material. [Means for solving the problem]
[0009] As a result of extensive investigations, the present inventors have found that the above problems can be solved by the following configuration, and have completed the present invention.
[0010] In one embodiment, the present invention comprises: Hydraulic material: 5% by mass or more and 45% by mass or less, Siliceous materials: 10% by mass or more and 55% by mass or less; Reinforcing fiber material: 1.5% by mass or more and 30% by mass or less; 5% to 60% by mass of calcium carbonate compounds with an aspect ratio of the average major axis to the average minor axis of 2 to 19 The present invention relates to an inorganic molded body comprising:
[0011] The inorganic molded body contains a calcium carbonate compound having an aspect ratio of 2 to 19 in an amount of 5% by mass to 60% by mass, and thus can sufficiently reduce warping and cracking during heating when used as a building material. Although the reason for this is unclear, it is presumed as follows. The inventors of the present invention have considered the cause of the heating behavior and have considered that the degree of shrinkage of the heated surface is large, which may cause cracks on the heated surface. It has also been presumed that the cracks on the heated surface are the cause of cracking and warping in the entire inorganic molded body. Furthermore, since the temperature rise of the back surface (the surface opposite to the heated surface) during heating is large, the temperature is rapidly transferred from the heated surface to the back surface, causing thermal shock in the thickness direction, which may lead to the occurrence of warping and cracking in the entire inorganic molded body. As a result of further investigation, the inventors of the present invention have found that by blending a high content of a calcium carbonate compound having a high aspect ratio into the inorganic molded body, it is possible to suppress the shrinkage of the heated surface and the rise in the back surface temperature during heating. The high aspect ratio calcium carbonate compound functions as a so-called reinforcing material, which can suppress the shrinkage of the heated surface and prevent the occurrence of cracks. In addition, the occurrence of warping during thermal shock can be reduced. Furthermore, by blending a high content of low thermal conductive calcium carbonate compound, the insulation properties in the thickness direction of the inorganic molded body are improved, and the increase in the back surface temperature can be suppressed, thereby suppressing the occurrence of thermal shock. As a result, it is presumed that warping and cracking can be prevented throughout the inorganic molded body.
[0012] In this specification, the term "calcium-based carbonate compound" refers to a compound containing calcium carbonate as a main component, and is a concept that allows the inclusion or coexistence of other subcomponents that may be incorporated during the manufacturing process, etc. The calcium carbonate content in the calcium-based carbonate compound is preferably 90 mass% or more. The content ratio of calcium carbonate in the calcium-based carbonate compound can be suitably measured by XRF (X-ray fluorescence analysis).
[0013] In one embodiment, the calcium carbonate compound is preferably a synthetic calcium carbonate compound. By using a synthetic calcium carbonate compound, which is a reaction product of calcium hydroxide and carbon dioxide, as the calcium carbonate compound, carbon dioxide generated secondarily in an industrial process can be reused, which contributes to reducing carbon dioxide emissions in the entire industrial process.
[0014] In one embodiment, the average particle size of the calcium carbonate compound is preferably 1.1 μm or more and 12.5 μm or less in terms of suppressing shrinkage of the heating surface.
[0015] In one embodiment, the calcium carbonate compound has an average major axis of 0.5 μm or more and 25 μm or less. In another embodiment, the calcium carbonate compound has a BET specific surface area of 1 m 2 / g or more 10m 2 By satisfying these conditions alone or in combination, the shrinkage of the heated surface and the rise in the back surface temperature during heating can be suppressed to a higher level.
[0016] In one embodiment, in the X-ray diffraction measurement of the calcium carbonate compound, the peak intensity I a Calcite peak intensity I c Ratio to I a / I c is preferably 0.02 or more. This makes it possible to efficiently impart a high aspect ratio to the calcium carbonate compound, and to reduce the occurrence of warping and cracking of the inorganic molded body to a higher level. [Brief description of the drawings]
[0017] [Figure 1] 1 is a SEM photograph of a calcium carbonate compound of Production Example 1-1 of the present invention. [Diagram 2] 1 is a SEM photograph of a calcium carbonate compound of Production Example 1-2 of the present invention. [Diagram 3]1 is a SEM photograph of a calcium carbonate compound of Production Example 1-3 of the present invention. [Figure 4] 1 is a SEM photograph of a calcium carbonate compound of Production Example 1-4 of the present invention. [Diagram 5] FIG. 2 is a partial perspective view showing a schematic diagram of a heating tester. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] An inorganic molded body according to an embodiment of the present invention will be described below, but the present invention is not limited to these embodiments.
[0019] <Inorganic molded body> The inorganic molded body contains a hydraulic material, a siliceous material, a reinforcing fiber material, and a calcium carbonate compound having a predetermined aspect ratio, each of which is contained in a specific amount.
[0020] (hydraulic material) Examples of hydraulic materials include cementitious materials, gypsum, lime, slag, etc. Examples of cementitious materials include commonly used cements, such as ordinary Portland cement, high-early-strength cement, moderate-heat cement, fly ash cement, blast furnace slag cement, and alumina cement. Examples of gypsum include anhydrous gypsum, hemihydrate gypsum, dihydrate gypsum, etc. Examples of slag include blast furnace slag, converter slag, etc. These hydraulic materials can be used alone or in combination of two or more.
[0021] The content of the hydraulic material is 5% by mass or more and 45% by mass or less, preferably 8% by mass or more and 42% by mass or less, and more preferably 10% by mass or more and 40% by mass or less, based on the total amount of materials constituting the inorganic molded body. By setting the content of the hydraulic material within the above range, it is possible to improve the physical properties such as bending strength and peel strength of the inorganic molded body, and to suppress the increase in bulk specific gravity of the inorganic molded body, thereby improving workability during construction.
[0022] (siliceous material) Examples of siliceous materials include materials containing a large amount of SiO2, such as silica sand, silica powder, silica fume, fly ash, diatomaceous earth, layered silicates (e.g., mica, talc, kaolin, bentonite), wollastonite, and lightweight aggregates (e.g., fly ash balloons, perlite, shirasu balloons, glass foams, etc.). These siliceous materials can be used alone or in combination of two or more. Talc, mica, and wollastonite can also be used as reinforcing fiber materials, which will be described later.
[0023] The content of the siliceous material is 10% by mass or more and 55% by mass or less, preferably 12% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 45% by mass or less, based on the total amount of materials constituting the inorganic molded body. If the content of the siliceous material is within the above range, it becomes possible to set the bending strength, bulk density, water absorption rate, dimensional stability, etc. of the inorganic molded body within the desired range. Note that, as the siliceous material, perlite, fly ash balloons, shirasu balloons, etc., having a unit volume mass of 0.5 g / cm are preferred. 3 When mixing the following lightweight aggregates, in order to prevent the bulk density from becoming too light, which would weaken strength such as bending strength and peel strength, it is preferable to use other siliceous materials in combination so that the content of lightweight aggregate is 20 mass% or less, based on the total amount of materials constituting the inorganic molded body.
[0024] (Reinforcing fiber materials) Examples of reinforcing fiber materials that can be used include pulps such as softwood pulp, hardwood pulp, pulps fibrillated with these pulps, and pulp made by defibrating waste paper, organic reinforcing fiber materials such as vinylon fiber, acrylonitrile fiber, and polypropylene fiber, and inorganic reinforcing fiber materials such as rock wool and glass fiber. These reinforcing fiber materials can be used alone or in combination of two or more.
[0025] In order to improve the strength and toughness of the inorganic molded body, the content of the reinforcing fiber material is 1.5% by mass or more and 30% by mass or less, preferably 3% by mass or more and 26% by mass or less, and more preferably 4% by mass or more and 22% by mass or less, based on the total amount of materials constituting the inorganic molded body. By setting the content of the reinforcing fiber material within the above range, it is possible to suppress the fibers from protruding from the surface of the inorganic molded body while exerting a sufficient reinforcing effect, thereby improving the smoothness. When an inorganic reinforcing fiber material with an average length of 1 mm to 50 mm is blended as the reinforcing fiber material, it is preferable to use another reinforcing fiber material in combination so that the content is 10% by mass or less, based on the total amount of materials constituting the inorganic molded body, in order to improve the smoothness of the inorganic molded body.
[0026] (Calcium carbonate compounds) The aspect ratio of the average major axis to the average minor axis of the calcium carbonate compound is 2 or more and 19 or less, preferably 2.5 or more and 17 or less, and more preferably 3 or more and 15 or less. It has been found that the shrinkage of the heated surface and the rise in the back surface temperature during heating can be suppressed. By setting the aspect ratio of the calcium carbonate compound within the above range, the calcium carbonate compound with a high aspect ratio effectively functions as a reinforcing material, suppressing the shrinkage of the heated surface and the rise in the back surface temperature, thereby preventing warping and cracking in the entire inorganic molded body.
[0027] The crystal structure of the calcium carbonate compound may be a calcite type, an aragonite type, or a combination thereof. In order to provide the calcium carbonate compound with the above aspect ratio, it is preferable that the calcium carbonate compound contains at least an aragonite type crystal structure.
[0028] In the X-ray diffraction measurement of the calcium carbonate compound, the peak intensity I a Calcite peak intensity I c Ratio to I a / I cis preferably 0.02 or more, more preferably 0.20 or more, and even more preferably 1.00 or more. This makes it possible to efficiently impart a high aspect ratio to the calcium carbonate compound, and to reduce the occurrence of warping and cracking of the inorganic molded body to a higher level.
[0029] The average particle size of the calcium carbonate compound measured by a laser diffraction method is preferably 1.1 μm or more and 12.5 μm or less, more preferably 1.5 μm or more and 12 μm or less, and even more preferably 2 μm or more and 11.5 μm or less, which can improve the dispersibility of the calcium carbonate compound and efficiently suppress the shrinkage of the heating surface.
[0030] The average major axis of the calcium carbonate compound is preferably 0.5 μm or more and 25 μm or less, more preferably 1 μm or more and 22 μm or less, and even more preferably 2 μm or more and 18 μm or less, which suppresses aggregation between the calcium carbonate compounds or between the calcium carbonate compounds and other components, and as a result, the shrinkage of the heating surface and the rise in the back surface temperature during heating can be suppressed to higher levels.
[0031] The BET specific surface area of the calcium carbonate compound is 1 m 2 / g or more 10m 2 / g or less, and 2 / g or more 9m 2 / g or less is more preferable, 2 / g or more 8m 2 This makes it possible to improve the dispersibility of the calcium carbonate compound, and as a result, it is possible to suppress the shrinkage of the heating surface and the rise in the back surface temperature during heating to a higher level.
[0032] The apparent specific gravity of the calcium carbonate compound is preferably 0.1 g / mL to 1.0 g / mL, more preferably 0.2 g / mL to 0.9 g / mL, and even more preferably 0.3 g / mL to 0.8 g / mL. By setting the apparent specific gravity of the calcium carbonate compound within the above range, the dispersibility of the calcium carbonate compound in the inorganic molded body is improved, and the shrinkage of the heating surface and the rise in the back surface temperature during heating can be suppressed to a higher level.
[0033] The calcium carbonate compound is preferably a synthetic calcium carbonate compound. By using a synthetic calcium carbonate compound, which is a reaction product of calcium hydroxide and carbon dioxide gas (carbon dioxide), as the calcium carbonate compound, carbon dioxide secondarily generated in the industrial process can be reused, which contributes to reducing carbon dioxide emissions in the entire industrial process. In addition, in the process of producing magnesium hydroxide from seawater, the calcium carbonate compound by-produced in the process of removing carbonates in seawater and seawater residue mainly composed of magnesium hydroxide can be used as the calcium carbonate compound source.
[0034] The content of the calcium carbonate compound is 5% by mass or more and 60% by mass or less, preferably 8% by mass or more and 55% by mass or less, and more preferably 12% by mass or more and 50% by mass or less, based on the total amount of materials constituting the inorganic molded body. By blending the low thermal conductive calcium carbonate compound in the above range, the heat insulation in the thickness direction of the inorganic molded body is improved, and the rise in the back surface temperature is suppressed, thereby suppressing the occurrence of thermal shock. As a result, warping and cracks in the entire inorganic molded body can be prevented.
[0035] (Method of producing calcium carbonate compound) The method for synthesizing calcium carbonate compounds is not particularly limited, and known manufacturing methods can be used.Typically, the carbon dioxide gas method is preferred in which carbon dioxide gas is blown into milk of lime (a slurry in which excess slaked lime is added to a saturated aqueous solution of slaked lime) to carbonate it.The carbon dioxide gas used in the carbon dioxide gas method can be the flue gas of a lime calciner installed near a calcium carbonate compound manufacturing plant, or the exhaust gas from a boiler, a waste incinerator, or the like.
[0036] A known method can also be used as a method for imparting a predetermined aspect ratio to a calcium carbonate compound based on the carbon dioxide gas method.Specific examples of the method include a method for producing a calcium carbonate compound in which the amount of carbon dioxide gas is adjusted at each stage in the carbonation process, a method for producing a calcium carbonate compound in which heating is performed at the carbonation stage, a method for producing a calcium carbonate compound in which needle-shaped light calcium carbonate compound is used as seed crystals in a slaked lime slurry, carbon dioxide gas is introduced into the slurry, and the seed crystals are grown to a desired particle size by a carbonation reaction, a method for producing a calcium carbonate compound in which an aragonite-type needle-shaped calcium carbonate compound is added to a slaked lime slurry and a carbonation reaction is performed while stirring with a high stirring power, a method for producing an aragonite-type calcium carbonate compound by adding a phosphoric acid compound, a method for producing a calcium carbonate compound by adding a sulfate compound to obtain a spindle-shaped calcium carbonate compound, a method for producing an aragonite-type calcium carbonate compound by using a slaked lime slurry prepared with an alkaline aqueous solution, and a method for producing an aragonite-type calcium carbonate compound by using a slaked lime slurry prepared with water containing magnesium ions. By using one or a combination of two or more of these methods, a calcium carbonate compound having an aragonite-type crystal structure can be efficiently produced.
[0037] The concentration of carbon dioxide varies depending on the type of exhaust gas generated from each combustion engine, but when carbonation efficiency is taken into consideration, it is preferably 1 volume % or more, more preferably 5 volume % or more, and even more preferably 10 volume % or more.
[0038] The carbonation temperature (the slurry temperature) is not particularly limited, and is preferably 15°C or higher and 100°C or lower, more preferably 20°C or higher and 90°C or lower, and even more preferably 25°C or higher and 80°C or lower.
[0039] The produced calcium carbonate compound may be filtered and dried to obtain a powder, or may be used as a calcium carbonate compound source in the form of a slurry or cake without being filtered or dried.
[0040] In addition to the carbon dioxide gas method, a water utilization method in which magnesium hydroxide is produced by adding slaked lime or the like to seawater and then removing magnesium from the residue (hereinafter referred to as "utilized water") is also preferred from the viewpoints of waste utilization and carbon dioxide reduction, in which an alkaline agent such as magnesium hydroxide is added to the residue and carbon dioxide gas is blown into it, from which magnesium hydroxide is removed. Furthermore, as described above, in the process of producing magnesium hydroxide from seawater, calcium-based carbonate compounds by-produced in the process of removing carbonates from seawater and seawater residue mainly composed of magnesium hydroxide can also be used as the calcium-based carbonate compound source.
[0041] (optional ingredient) In addition to the above materials, in order to impart various functions to the inorganic molded body, various materials such as resin hollow bodies, wood chips, wood powder, resin powder, defoamers, flocculants, water repellents, thickeners (methyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, etc.), dispersants, etc. can be mixed into the inorganic molded body depending on the purpose. It is also possible to appropriately add recycled materials obtained by crushing scraps generated during processing of the inorganic molded body.
[0042] (Method for producing inorganic molded body) The method for producing the inorganic molded body according to this embodiment is not particularly limited, and generally used methods such as papermaking, extrusion molding, flow-on molding, pouring molding, and press (compression) molding can be used. The inorganic molded body can be obtained by subjecting a green sheet molded by these methods to a patterning process such as press dehydration or embossing, and then curing the green sheet at room temperature, steam curing, autoclave curing, etc. Furthermore, the green sheet may be dried, and shaped or painted as necessary.
[0043] When the inorganic molded body is produced by a papermaking method, the aspect ratio of the calcium carbonate compound is preferably 4 or more and 19 or less, more preferably 6 or more and 18 or less, and even more preferably 8 or more and 17 or less.
[0044] When the inorganic molded body is produced by extrusion molding, the aspect ratio of the calcium carbonate compound is preferably 2 or more and 12 or less, more preferably 2.5 or more and 10 or less, and even more preferably 3 or more and 8 or less.
[0045] (Uses of inorganic molded bodies) The use of the inorganic molded body is not particularly limited, and it can be suitably used as a performance maintaining material such as a wall material, a floor material, a roofing material, various boards, external decorative members, interior and exterior finishing materials such as fittings, a sealing material, a heat insulating material, a sound absorbing material, a waterproofing material, etc. The inorganic molded body is preferably a cement-based molded body containing a cementitious material, and more preferably a calcium silicate molded body. Among them, the molded body is more preferably a molded board.
[0046] The inorganic molded body may be a concrete structure. The concrete structure is composed of a hardened body of a hydraulic composition. The hydraulic composition is composed of a powder containing, in addition to calcium carbonate, at least one of blast furnace slag, an expansive material, slaked lime, quicklime, fly ash, and a cementitious material. As the calcium carbonate, the above-mentioned calcium carbonate compound can be suitably used. As the cementitious material, the cementitious material shown in the hydraulic material can be suitably used.
[0047] In addition to the above hydraulic composition, aggregates such as sand and gravel, chemicals such as chemical admixtures for concrete, and fiber materials made of metals or polymeric materials may be mixed to prepare a hydraulic composition mixture.
[0048] The hardened hydraulic composition is obtained by hardening a paste obtained by kneading the hydraulic composition with water, and the hardened hydraulic composition mixture is obtained by hardening a kneaded product (corresponding to fresh mortar or fresh concrete) obtained by kneading the hydraulic composition with water, and corresponds to mortar or concrete. EXAMPLES
[0049] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. Measurements and evaluations of physical properties, etc. were performed as follows.
[0050] <Evaluation of calcium carbonate compounds> The calcium carbonate compounds obtained in each production example were analyzed as follows. The analysis results are shown in Table 1 and Figures 1 to 4.
[0051] (1) BET specific surface area The sample powder was pretreated in a nitrogen gas atmosphere at approximately 130°C for approximately 30 minutes using an 8-unit preheat unit (MOUNTECH), and the BET specific surface area (m2) was measured by nitrogen gas adsorption using a Macsorb HM Model-1208 (MOUNTECH) BET specific surface area measuring device. 2 / g) was measured.
[0052] (2) Average particle size by laser diffraction method 50 mL of ethanol was placed in a 100 mL beaker, and about 0.2 g of the sample powder was placed in the 100 mL beaker. The dispersion was prepared by ultrasonic treatment for 3 minutes (Tomy Seiko UD-201). The volumetric D of this dispersion was measured using a laser diffraction particle size distribution analyzer (Nikkiso Microtrac HRA Model 9320-X100).50 The value was measured as the average particle size (μm).
[0053] (3) 46° (aragonite) peak intensity I by XRD measurement a 29° (calcite) peak intensity I c Calculating the ratio to The sample powder was pressed and fixed on a specified sample stage with a spatula, and then measured using an XRD device (MiniFlex600-C, manufactured by Rigaku Corporation) to perform identification analysis as a crystalline substance. Note that, at the measurement angle 2θ, the peak appearing at approximately 29° is the main peak of calcite, and the peak appearing at approximately 46° is the main peak of aragonite. From this, the 46° (aragonite) peak intensity I a 29° (calcite) peak intensity I c Ratio to (I a / I c ) was sought.
[0054] (4) Calculation of average major axis, average minor axis and aspect ratio by scanning electron microscope observation Double-sided tape was attached to an aluminum sample stage, and the sample powder was applied on top of it by tracing it with a spatula. After platinum deposition, the particle image of the sample powder was photographed at 2,000 times magnification using a scanning electron microscope (FE-SEM: S-4700 manufactured by Hitachi, Ltd.). SEM images are shown in Figures 1 to 4. For the obtained SEM images, 20 particles were randomly selected from the images using image analysis software (Image J), and the average values of the major axis, minor axis, and aspect ratio (ratio of major axis to minor axis) of the primary particles were calculated. Specifically, the major axis and minor axis were measured by the following procedure. For one randomly selected particle image, the length of the straight line with the maximum span was taken as the "major axis," and the span on the particle image of the straight line that gives the major axis (major axis) at the center of the straight line (major axis) that is perpendicular to the major axis was taken as the "minor axis."
[0055] (5) Apparent specific gravity The apparent specific gravity of the sample powder was measured in accordance with JIS K6220.
[0056] <Production of calcium carbonate compounds> [Production Example 1-1] Calcium carbonate compound (aspect ratio 10.4) 6980g of slaked lime powder (calculated as CaO), 630g of aragonite seed crystal powder, and 500g of disodium hydrogen phosphate dodecahydrate were prepared, and each was added to a 220L SUS vessel with a baffle plate and filled with 180L of water, while stirring, to prepare a mixed slurry of the raw materials. The temperature was then raised to 70°C, and the mixture was stirred at 150 rpm using a stirrer equipped with one turbine blade at that temperature. A pipe for extracting exhaust gas was connected to the exhaust outlet of a steam production boiler that uses LNG as fuel, and the exhaust gas was drawn in using a test blower. The CO2 concentration was measured using a CO2 concentration meter (XP-3140 manufactured by Shin Cosmos Electric Co., Ltd.), which showed a CO2 concentration of 10% by volume. Exhaust gas was introduced into the 220L SUS vessel described above using a test blower at a speed of 100L / min, and the reaction was carried out for 7 hours. The mixture was then filtered, washed with about five times as much water as the solid content, dried at 110°C for 24 hours, and pulverized to obtain a sample powder of a calcium carbonate compound.
[0057] [Production Example 1-2] Calcium carbonate compound (aspect ratio 18.2) A sample powder of calcium carbonate compound was obtained by the same procedure as in Production Example 1-1, except that the amount of milk of lime was 3,400 g (calculated as CaO), the amount of the material obtained in Production Example 1-1 was 310 g as seed crystals of aragonite, and the amount of disodium hydrogen phosphate dodecahydrate was 240 g.
[0058] [Production Example 1-3] Calcium carbonate compound (aspect ratio 2.7) A sample powder of calcium carbonate compound was obtained by the same procedure as in Production Example 1-1, except that 7,170 g of milk of lime (calculated as CaO) was prepared, no aragonite seed crystals or disodium hydrogen phosphate dodecahydrate was added, and the reaction temperature was set at 40°C.
[0059] [Production Example 1-4] Calcium carbonate compound (aspect ratio 1.2) A sodium carbonate solution was prepared by adding 5940 g of sodium carbonate reagent (manufactured by Wako Pure Chemical Industries, purity 99.8%) to a 220 L SUS container with a baffle plate, which was filled with 100 L of water, while stirring. Meanwhile, 1000 L of water was placed in a 2000 L polyethylene container, and 6940 g of calcium chloride reagent (manufactured by Wako Pure Chemical Industries, purity 95%) was added to the container while stirring to prepare a calcium chloride solution (Ca 2+ A calcium carbonate compound powder sample was prepared by carrying out the same procedure as in Production Example 1-1, except that 100 L of the sodium carbonate aqueous solution was added at once while stirring the calcium chloride aqueous solution, and the reaction was continued for about 30 minutes.
[0060] [Table 1]
[0061] <Production of Inorganic Molded Body> Inorganic molded bodies were manufactured by the papermaking method and extrusion molding method according to the following procedures. The amounts of the components used are all shown in "parts by mass" unless otherwise specified. In the table below, "-" indicates that the corresponding component was not used.
[0062] [Example 1-1] Production of inorganic molded body by papermaking method The materials shown in Table 2 below were put into a plastic container and mixed by stirring to obtain a raw material slurry. The calcium carbonate compound of Production Example 1-1 was used as the calcium carbonate compound. The raw material slurry was divided and put into a filter lined with felt, and a laminate (long side 28 mm x short side 24 mm x thickness 14 mm) was produced while performing suction filtration with a vacuum pump. The laminate was removed from the filter and subjected to dehydration pressing. The thickness after pressing was 13 mm. After autoclave curing (curing pressure (gauge pressure) 9 kgf; curing time 12 hours), the pressed body was dried in a dryer (105°C) for 24 hours. Both sides were polished with a sander to adjust the thickness to 12 mm, and an inorganic molded body was obtained.
[0063] [Example 1-2] Production of inorganic molded body by papermaking method An inorganic formed body was obtained in the same manner as in Example 1-1, except that the calcium carbonate compound of Production Example 1-2 was used as the calcium carbonate compound.
[0064] [Example 1-3] Production of inorganic molded body by papermaking method An inorganic formed body was obtained in the same manner as in Example 1-1, except that the calcium carbonate compound of Production Example 1-3 was used as the calcium carbonate compound.
[0065] [Comparative Example 1-1] Production of inorganic molded body by papermaking method An inorganic formed body was obtained in the same manner as in Example 1-1, except that the calcium carbonate compound of Production Example 1-4 was used as the calcium carbonate compound.
[0066] [Comparative Example 1-2] Production of inorganic molded body by papermaking method An inorganic molded body was obtained in the same manner as in Example 1-1, except that the materials shown in Table 2 below were used and no calcium carbonate compound was added.
[0067] [Comparative Example 1-3] Production of inorganic molded body by papermaking method An inorganic molding was obtained in the same manner as in Example 1-1, except that a calcium carbonate compound having an aspect ratio of 25 was used as the calcium carbonate compound. However, the calcium carbonate compound was broken during molding and could not maintain its original shape, so no evaluation was performed.
[0068] [Examples 1-4 to 1-10] Production of inorganic molded bodies by papermaking method An inorganic molded body was obtained in the same manner as in Example 1-1, except for using the materials shown in the following Table 3. For reference, Table 3 also lists the materials and evaluations of Examples 1-1 to 1-3 and Comparative Example 1-2.
[0069] <Evaluation of inorganic molded bodies> The inorganic molded bodies produced by the papermaking method in the examples and comparative examples were evaluated as follows. The results are shown in Tables 2 and 3.
[0070] (bulk density) The bulk density was measured in accordance with JIS A 5430.
[0071] (Heating test) The heating test was carried out with the following equipment and procedure. Figure 5 is a partial perspective view that shows a schematic diagram of the heating tester. As shown in Figure 5, an electric heater was used as the heat source, and fireproof material was installed between the test specimen and the heat source so that the temperature could be stabilized at around 900°C, and the temperature of the back side of the test specimen could be measured with a thermocouple. Specifically, an electric heater (1.2 kW heater) was used as the heat source equipment, and a K thermocouple and a temperature regulator were connected. In addition, each thermocouple was connected to a data logger. The distance between the heating surface of the test specimen and the heat source was fixed at approximately 70 mm.
[0072] The test procedure was as follows. (1) A scrap board was placed and preheating was performed up to 902°C, after which heating was performed once. (2) The test specimen was inserted after the heated surface had cooled below 200°C. (3) A thermocouple was placed in the center of the back surface of the test specimen (top surface in the figure), and a calcium silicate plate (approximately 30 mm x 70 mm) and a weight were placed on top and fixed in place. (4) Heating was started, and the specimen was left for a specified time (45 minutes), after which the temperatures of the front and back sides were recorded with a data logger. During this time, the temperature of the electric heater was set to 902°C on the heating side, and was controlled with a temperature controller with a lower limit of 900°C. The data logger also measured the temperature every 10 seconds, and the data was recorded at this interval. (5) After the test was completed, the test specimens were removed and the following items were measured (each item was also measured before the test): Dimensions: The length and width of the back surface and the heated surface were measured with a caliper. The area of the heated surface (mm 2 ) was calculated, and the heating surface shrinkage (%) was calculated based on the following formula: Heating surface shrinkage (%) = {|S1-S0| / S0} x 100 (In the formula, S0 is the area of the heated surface before the test, and S1 is the area of the heated surface after the test.) Warpage: The specimen was placed on a steel plate, and the height of the center of each side of the specimen from the steel plate was measured with a thickness gauge, and the average value (mm) was calculated. This average value was taken as the warpage after heating (mm). - Photographs of the sample before and after the test (photos showing the extent of cracks before and after heating)
[0073] [Table 2]
[0074] [Table 3]
[0075] The inorganic molded body of the Example was superior to the Comparative Example in terms of shrinkage on the heated surface, temperature rise on the reverse surface, and warpage after heating. Furthermore, the inorganic molded body of the Example did not develop cracks after heating (not shown).
[0076] [Example 2-1] Production of inorganic molded body by extrusion molding method The materials shown in Table 3 below were put into an Omni Mixer and the raw materials were dry-mixed for 3 minutes. The calcium carbonate compound of Production Example 1-1 was used as the calcium carbonate compound. Next, water was added and wet-mixed for 2 minutes. The raw materials after wet mixing were kneaded with an Ishikawa extruder, and then extrusion-molded with the Ishikawa extruder. This produced a molded body (long side 600 mm x short side 190 mm x thickness 13 mm). After obtaining the molded body, it was put into a thermostatic chamber set at 60°C / 98% and subjected to primary curing, and then the pressure was increased to 9 kgf and autoclave curing was performed for 12 hours. Both sides of the molded body were polished with a sander to make the thickness 12 mm, producing an inorganic molded body.
[0077] [Example 2-2] Production of inorganic molded body by extrusion molding method An inorganic formed body was obtained in the same manner as in Example 2-1, except that the calcium carbonate compound of Production Example 1-2 was used as the calcium carbonate compound.
[0078] [Example 2-3] Production of inorganic molded body by extrusion molding method An inorganic formed body was obtained in the same manner as in Example 2-1, except that the calcium carbonate compound of Production Example 1-3 was used as the calcium carbonate compound.
[0079] [Comparative Example 2-1] Production of inorganic molded body by extrusion molding method An inorganic formed body was obtained in the same manner as in Example 2-1, except that the calcium carbonate compound of Production Example 1-4 was used as the calcium carbonate compound.
[0080] [Comparative Example 2-2] Production of inorganic molded body by extrusion molding method An inorganic molded body was obtained in the same manner as in Example 2-1, except that the materials and contents shown in Table 3 below were used and no calcium carbonate compound was added.
[0081] [Comparative Example 2-3] Production of inorganic molded body by extrusion molding method An inorganic molding was obtained in the same manner as in Example 2-1, except that a calcium carbonate compound having an aspect ratio of 25 was used as the calcium carbonate compound. However, the calcium carbonate compound was broken during molding and could not maintain its original shape, so no evaluation was performed.
[0082] <Evaluation of inorganic molded bodies> The inorganic molded bodies produced by extrusion molding in the Examples and Comparative Examples were evaluated as follows. The results are shown in Table 4.
[0083] (bulk density) The bulk density was measured in accordance with JIS A 5430.
[0084] (3-point bending test) The three-point bending test was performed in accordance with JIS A 5430. The results were used to calculate the strength (N / mm 2 ) was decided.
[0085] (Heating test) The measurement was carried out in the same manner as in the papermaking method.
[0086] [Table 4]
[0087] The inorganic molded bodies of the Examples were superior to the Comparative Examples in both the heated surface shrinkage and the warpage after heating. Furthermore, the inorganic molded bodies of the Examples did not develop cracks after heating (not shown).
Claims
1. 5% by mass or more and 45% by mass or less of hydraulic material, A silicate material is 10% by mass or more and 55% by mass or less, Reinforcing fiber material: 1.5% by mass or more and 30% by mass or less; 5% by mass to 60% by mass of calcium carbonate compounds having an aspect ratio of the average major axis to the average minor axis of 2 to 19 The inorganic molded body includes each of the following:
2. 2. The inorganic formed body according to claim 1, wherein the calcium carbonate compound is a synthetic calcium carbonate compound.
3. 2. The inorganic molded product according to claim 1, wherein the calcium carbonate compound has an average particle size of 1.1 μm or more and 12.5 μm or less as measured by a laser diffraction method.
4. 2. The inorganic molded body according to claim 1, wherein the calcium carbonate compound has an average major axis of 0.5 μm or more and 25 μm or less.
5. The BET specific surface area of the calcium carbonate compound is 1 m 2 / g or more 10m 2 The inorganic molded body according to claim 1, wherein the molecular weight is 1 / g or less.
6. In the X-ray diffraction measurement of the calcium carbonate compound, the peak intensity I of aragonite a Calcite peak intensity I c Ratio to I a / I c The inorganic molded body according to claim 1 , wherein is 0.02 or more.
Citation Information
Patent Citations
Thermoplastic resin composition and molded article composed thereof
JP1989278566A
Hydroxyapatite-calcium carbonate composite particle and manufacturing method therefor
JP2005231920A
Calcium silicate molded body and its manufacturing method
JP2014108918A
Fiber-reinforced carbonated cement molded product and method for producing same
WO2018003612A1
Calcium carbonate water slurry and method for producing calcium carbonate water slurry
WO2023074608A1